2019
DOI: 10.3390/ijms20236038
|View full text |Cite
|
Sign up to set email alerts
|

PatJAZ6 Acts as a Repressor Regulating JA-Induced Biosynthesis of Patchouli Alcohol in Pogostemon Cablin

Abstract: The JASMONATE ZIM DOMAIN (JAZ) proteins act as negative regulators in the jasmonic acid (JA) signaling pathways of plants, and these proteins have been reported to play key roles in plant secondary metabolism mediated by JA. In this study, we firstly isolated one JAZ from P. cablin, PatJAZ6, which was characterized and revealed based on multiple alignments and a phylogenic tree analysis. The result of subcellular localization indicated that the PatJAZ6 protein was located in the nucleus of plant protoplasts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In P. cablin , four TF families have been reported, including PatMYB46 in the MYB family, PatMYC2b1 and PatMYC2b2 in the bHLH family, PatGT-1 in the TH family and SPL10 in the SBP family. Yu et al (2015) found that overexpression of SPL10 in P. cablin could increase the synthesis of PA. Wang et al (2019) found that PatMYC2b1 and PatMYC2b2 could bind to the PatJAZ6 protein to regulate PA synthesis. Chen et al (2020) found that overexpression of PatMYB46 in P. cablin could increase the content of PA. Li et al (2021) found that overexpression of PatGT-1 in P. cablin could reduce the content of PA and revealed that PatGT-1 negatively regulates PA biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In P. cablin , four TF families have been reported, including PatMYB46 in the MYB family, PatMYC2b1 and PatMYC2b2 in the bHLH family, PatGT-1 in the TH family and SPL10 in the SBP family. Yu et al (2015) found that overexpression of SPL10 in P. cablin could increase the synthesis of PA. Wang et al (2019) found that PatMYC2b1 and PatMYC2b2 could bind to the PatJAZ6 protein to regulate PA synthesis. Chen et al (2020) found that overexpression of PatMYB46 in P. cablin could increase the content of PA. Li et al (2021) found that overexpression of PatGT-1 in P. cablin could reduce the content of PA and revealed that PatGT-1 negatively regulates PA biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Only by understanding the biosynthetic pathways and regulatory mechanisms of PA can we improve the production of patchouli oil and PA to meet consumer demand by means of metabolic engineering. Recently, a number of studies have focused on individual key enzyme genes and transcription factors to elucidate the biosynthetic mechanism of PA ( Yan et al, 2021 ; Zhang et al, 2019b , 2019c ; Yu et al, 2015 ; Wang et al, 2019 ; Chen et al, 2020 ; Li et al, 2021 ). There are also some reports on the regulation of the synthesis of PA by exogenous plant hormones, circadian rhythms and developmental stages ( Wang et al, 2019 ; Chen et al, 2019 ; Ouyang et al, 2016 ; Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patchoulol synthase catalyzes FFP to produce patchoulol (Deguerry et al, 2006;Ekramzadeh et al, 2020;Faraldos et al, 2010), which is essential for patchoulol biosynthesis and Pogostemonis herba quality. In patchouli, most studies on PTS have focused on transcriptional regulation of enzymatic functions and regulation by hormones (Chen et al, 2019(Chen et al, , 2020(Chen et al, , 2022bHuang et al, 2022;Wang et al, 2019), but studies on protein-protein interactions in the patchoulol biosynthetic pathway are lacking. Hence, in our previous studies, a GST-pull-down assay was performed to screen interacting proteins in crude protein of P. cablin using the GST-PcPTS as bait (Zhong, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the DELLA protein RGA was reported to promote MYC2-dependent JA signaling by competitively binding to JAZ1 (jasmonate ZIM-domain) [ 49 , 50 ]. JAZ proteins in Arabidopsis have been shown to be transcriptional repressors in the JA signaling pathway, and they interact with and repress the function of the JA response gene MYC2 transcription factor [ 51 ]. When sufficient JA is synthesized in plants, it leads to the degradation of JAZ by the 26S protein hydrolase pair, allowing the release of active MYC2, which initiates downstream genes [ 52 ], regulating terpene synthesis or plant development.…”
Section: Discussionmentioning
confidence: 99%